NanoSIMS Imaging Reveals the Impact of Ligand-ASO Conjugate Stability on ASO Subcellular Distribution - Emma Kay; Rouven Stulz; Cécile Becquart; Jelena Lovric; Carolina Tängemo; Aurélien Thomen; Dženita Baždarević; Neda Najafinobar; Anders Dahlén; Anna Pielach; Julia Fernandez-Rodriguez; Roger Strömberg; et al. (Pharmaceutics, 2022)
The delivery of antisense oligonucleotides (ASOs) to specific cell types via targeted endocytosis is challenging due to the low cell surface expression of target receptors and inefficient escape of ASOs from the endosomal pathway. Conjugating ASOs to glucagon-like peptide 1 (GLP1) leads to efficient target knockdown, specifically in pancreatic β-cells. It is presumed that ASOs dissociate from GLP1 intracellularly to enable an ASO interaction with its target RNA. It is unknown where or when this happens following GLP1-ASO binding to GLP1R and endocytosis. Here, we use correlative nanoscale secondary ion mass spectroscopy (NanoSIMS) and transmission electron microscopy to explore GLP1-ASO subcellular trafficking in GLP1R overexpressing HEK293 cells. We isotopically label both eGLP1 and ASO, which do not affect the eGLP1-ASO conjugate function. We found that the eGLP1 peptide and ASO are not detected at the same level in the same endosomes, within 30 min of GLP1R-HEK293 cell exposure to eGLP1-ASO. When we utilized different linker chemistry to stabilize the GLP1-ASO conjugate, we observed more ASO located with GLP1 compared to cell incubation with the less stable conjugate. Overall, our work suggests that the ASO separates from GLP1 relatively early in the endocytic pathway, and that linker chemistry might impact the GLP1-ASO function.